A Comprehensive review of functional ingredients, especially bioactive compounds present in pumpkin peel, flesh and seeds, and their health benefits. (October 2022) - Hussain, Ashiq; Kausar, Tusneem; Sehar, Sawera; Sarwar, Ayesha; Ashraf, Abdul Haseeb; Jamil, Muhammad Abdullah; Noreen, Saima; Rafique, Ayesha; Iftikhar, Khansa; Quddoos, Muhammad Yousaf; Aslam, Jawaid; Majeed, Muhammad Abid
Highlights: Pumpkin waste streams, instead of discarding, must be utilized as health promoting foods. Pumpkin peel can be utilized to extract pectin, polysaccharides and fiber. Pumpkin flesh contains appreciable amounts of carotenoids, minerals and polysaccharides. Pumpkin seeds are good source of essential oils, proteins, phenols and minerals. Consumption of pumpkin fractions should be strategy to combat immune related diseases. Abstract: Pumpkin ( Cucurbita maxima ), belonging to family Cucurbitaceae, is a well-known edible plant, cultivated and abundantly used as herbal medicine and functional food. This review aimed to investigate functional and nutraceutical constituents present in all three parts (peel, flesh and seeds) of pumpkin, and health benefits of these nutrients. Pumpkin fractions are rich source of nutritional components like oils, proteins, carbohydrates and minerals. Certain classes of phytochemical compounds including, phenolics, flavonoids, tocopherols, carotenoids, terpenoids, cucurbitacin, moschatin and phytosterols have been discovered from pumpkin fractions. Considerable evidences from several epidemiological studies upon animals and human trials have been present about pharmacological actions of pumpkin bio actives. Therapeutically, pumpkin peel, flesh and seeds contain active ingredients, acting as effective antioxidants and antimicrobial agents. No part of pumpkin fruit should be discarded during processing as these parts possess excellent phytochemistry, capable of impacting positive health impacts. All these parts of pumpkin can be used in the form of powders or extracts to isolate and characterize bio-actives and to utilize them in food and pharmaceutical industries as therapeutic agents. Instead of consumption in raw form, technologies should be implemented to develop novel and innovative nutraceuticals and pharma foods from health beneficial constituents of pumpkin.